Twelve-month and lifetime prevalence of mental disorders in cancer patients - Kuhnt, Susanne; Brähler, Elmar; Faller, Hermann; Härter, Martin; Keller, Monika; Schulz, Holger; Wegscheider, Karl; Weis, Joachim; Boehncke, Anna; Hund, Bianca; Reuter, Katrin; Richard, Matthias; et al. (Psychotherapy and psychosomatics, 2016)
Background: Psychological problems are common in cancer patients. For the purpose of planning psycho-oncological interventions and services tailored to the specific needs of different cancer patient populations, it is necessary to know to what extent psychological problems meet the criteria of mental disorders. The purpose of this study was to estimate the 12-month and lifetime prevalence rates of mental disorders in cancer patients. Methods: A representative sample of patients with different tumour entities and tumour stages (n = 2,141) in outpatient, inpatient and rehabilitation settings underwent the standardized computer-assisted Composite International Diagnostic Interview for mental disorders adapted for cancer patients (CIDI-O). Results: The overall 12-month prevalence for any mental disorder was 39.4% (95% CI: 37.3-41.5), that for anxiety disorders was 15.8% (95% CI: 14.4-17.4), 12.5% (95% CI: 11.3-14.0) for mood disorders, 9.5% (95% CI: 8.3-10.9) for somatoform disorders, 7.3% (95% CI: 6.2-8.5) for nicotine dependence, 3.7% (95% CI: 3.0-4.6) for disorders due to general medical condition, and 1.1% (95% CI: 0.7-1.6) for alcohol abuse or dependence. Lifetime prevalence for any mental disorder was 56.3% (95% CI 54.1-58.6), that for anxiety disorders was 24.1% (95% CI: 22.3-25.9), 20.5% (95% CI: 18.9-22.3) for mood disorders, 19.9% (95% CI: 18.3-21.7) for somatoform disorders, 18.2% (95% CI: 16.6-20.0) for nicotine dependence, 6.4% (95% CI: 5.4-7.6) for alcohol abuse or dependence, 4.6% (95% CI: 3.8-5.6) for disorders due to general medical condition, and 0.2% (95% CI: 0.1-0.6) for eating disorders. Conclusions: Mental disorders are highly prevalent in cancer patients, indicating the need for provision of continuous psycho-oncological support from inpatient to outpatient care, leading to an appropriate allocation of direct personnel and other resources.
Gesehen am 03.06.2020